Exploration of the Integration of Transparent Bustier and Fabric Spiral as Aesthetic Elements in Couture Fashion - Devita Intan Nuraini; Khasna Auliasifa; Widowati Widowati; Dian Saputra (Jurnal Penelitian Pendidikan, 2026)
The development of couture fashion encourages designers to continuously explore construction techniques and textile manipulation to create garments with strong aesthetic value and distinctive visual characteristics. One of the innovations that can be applied is the combination of transparent bustier construction and three-dimensional fabric spiral manipulation. This study aimed to explore the application of a transparent bustier and fabric spiral as aesthetic elements in couture fashion and to evaluate the feasibility of the resulting garment. The research employed a practice-based research approach with descriptive quantitative and qualitative methods. Data were collected through direct observation during the creation process, semi-structured interviews with fashion practitioners, documentation, and product feasibility assessments conducted by three fashion experts consisting of a fashion lecturer, a couture practitioner, and a fashion designer. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the integration of a transparent bustier and three-dimensional organza fabric spiral successfully created a distinctive visual focal point and enhanced the artistic value of the couture garment. The feasibility assessment obtained a total score of 437 out of a maximum score of 450, resulting in a feasibility percentage of 97.11%, categorized as very feasible. The highest scores were achieved in the aspects of aesthetics and product uniqueness. Therefore, the exploration of transparent bustier and fabric spiral can be considered an innovative design approach that contributes to the development of couture fashion with high aesthetic quality and strong visual identity.